The versatility of biodegradable temporising matrix – A 63 paediatric case series with complex wounds. Issue 2 (April 2023) - Storey, Kristen; Lalloz, Minella; Choy, Kay-Tai; McBride, Craig A.; McMillan, Catherine; Das Gupta, Romi; Patel, Bhaveshkumar; Choo, Kelvin; Stefanutti, Giorgio; Borzi, Peter; Phua, Yun; Bade, Stuart; et al.
Highlights: Biodegradable temporising matrix is a completely synthetic product. We have shown promising results in the paediatric population using Biodegradable temporising matrix for burns and complex wounds. Biodegradable temporising matrix converts complex wounds to simple wounds. Provides an option for early wound closure. Abstract: Intro: Treating complex paediatric wounds is a challenge for many clinicians. Biodegradable Temporising Matrix (BTM) is a completely synthetic product that has shown promise in adults with acute burns, complex wounds, and reconstructive procedures. Currently, there is little documentation regarding the use of BTM in the paediatric population. Method: A retrospective chart review was conducted of all children who required application of BTM for wound treatment. Children were grouped into categories according to the type of injury or condition including thermal, friction, and electrical injuries, scar reconstruction, and various wound defects. Outcomes of interest included infection rates, time to application of BTM and split-thickness skin graft (SSG), dressings used, and overall functional and cosmetic outcomes. Results: 63 children were identified. Thermal (19/63) and friction (10/63) injuries represented the largest groups. Males accounted for 68 % of total children with lower limbs and feet most often affected. The median time for application of BTM was 7.5 days and 27 days from time of application of BTM to SSG. BTM provided satisfactory options for early wound closure and the ability to convert complex wounds, however it still does not negate the need for scar management. Conclusion: From our review, BTM is a versatile product that has shown positive results for the treatment of complex wounds in the paediatric population. It represents the largest consecutive BTM case series in either adult or paediatric populations to date.